A rigorous derivation of power spectrum of fractional Gaussian noise - LI, MING (WORLD SCIENTIFIC PUBL CO PTE LTD, 2006)
This letter gives a concise and rigorous derivation of the power spectrum density function of fractional Gaussian noise (fGn).